2012
DOI: 10.1007/s00436-012-2862-5
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA and morphology show independent evolutionary histories of bedbug Cimex lectularius (Heteroptera: Cimicidae) on bats and humans

Abstract: The bedbug, Cimex lectularius, is a well-known human ectoparasite that is reemerging after a long absence of several decades in developed countries of North America and Western Europe. Bedbugs' original hosts were likely bats, and the bedbugs are still common in their roosts. Using morphometry and sequences of mitochondrial cytochrome oxidase subunit I and 16S genes, we showed that the populations on bats and humans are largely isolated and differ in morphology. The character of the morphological difference su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
109
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(121 citation statements)
references
References 46 publications
9
109
3
Order By: Relevance
“…Rather, our results suggest that paternal mtDNA leakage is likely responsible for heteroplasmy because in three populations (AR5-1, RC2-1, and RC3-1), identical heteroplasmic mtDNA haplotypes are present. Furthermore, these haplotypes have been recorded previously in samples sequenced within Europe (Balvin et al 2012, Booth et al 2015. Additionally, some haplotypes in this study differed by three mutations at the region of COI sequenced, each time with the mutation present in the third codon position.…”
Section: Resultssupporting
confidence: 65%
See 2 more Smart Citations
“…Rather, our results suggest that paternal mtDNA leakage is likely responsible for heteroplasmy because in three populations (AR5-1, RC2-1, and RC3-1), identical heteroplasmic mtDNA haplotypes are present. Furthermore, these haplotypes have been recorded previously in samples sequenced within Europe (Balvin et al 2012, Booth et al 2015. Additionally, some haplotypes in this study differed by three mutations at the region of COI sequenced, each time with the mutation present in the third codon position.…”
Section: Resultssupporting
confidence: 65%
“…The second haplotype in each specimen differed from haplotype 1 by either one or three nucleotide substitutions. Haplotype 2, which differs from haplotype 1 at a single base, has previously been reported in C. lectularius (Balvin et al 2012) and was found in three of the five specimens analyzed; the remaining two haplotypes had not been reported in C. lectularius. Each distinct haplotype resulted from synonymous third position codon mutations.…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…The same had long been thought about the bedbug Cimex lectularius (e.g. Sailer 1952;Usinger 1966), but new results suggest an early sympatric speciation on humans and bats for different populations of bed bugs (Balvín et al 2012). Although various pathogens have been identified from Cimicidae (e.g.…”
Section: Introductionmentioning
confidence: 87%
“…Hwang et al 2005, Romero et al 2007, Reinhardt et al 2008, Weeks et al 2010, Balvín et al 2012, Booth et al 2015, including cytogenetic studies using modern methods by Grozeva et al (2010 and the detailed analysis of variable karyotype by Sadílek et al (2013). As it is generally very important to improve methodological approach to research, we used the spreading method for preparing C. lectularius chromosome slides.…”
Section: Introductionmentioning
confidence: 99%